2009
DOI: 10.1074/jbc.m109.030536
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Na,K-ATPase Subunit Abundance by Translational Repression

Abstract: The Na,K-ATPase is an ␣␤ heterodimer responsible for maintaining fluid and electrolyte homeostasis in mammalian cells. We engineered Madin-Darby canine kidney cell lines expressing ␣ 1 FLAG, ␤ 1 FLAG, or ␤ 2 MYC subunits via a tetracycline-regulated promoter and a line expressing both stable ␤ 1 MYC and tetracycline-regulated ␤ 1 FLAG to examine regulatory mechanisms of sodium pump subunit expression. When overexpression of exogenous ␤ 1 FLAG increased total ␤ subunit levels by >200% without changes in ␣ subun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 57 publications
5
10
0
Order By: Relevance
“…Similar to our data, expression of flag-conjugated sheep β 1 subunit in MDCK cells did not alter mRNA level of endogenous subunits or the amount of the α 1 subunit but decreased the level of the endogenous β 1 subunit (37). Based on these results, the authors concluded that translation of the endogenous β 1 subunit is repressed by expression of the exogenous β 1 subunit by an unknown mechanism (37).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to our data, expression of flag-conjugated sheep β 1 subunit in MDCK cells did not alter mRNA level of endogenous subunits or the amount of the α 1 subunit but decreased the level of the endogenous β 1 subunit (37). Based on these results, the authors concluded that translation of the endogenous β 1 subunit is repressed by expression of the exogenous β 1 subunit by an unknown mechanism (37).…”
Section: Discussionsupporting
confidence: 90%
“…Based on these results, the authors concluded that translation of the endogenous β 1 subunit is repressed by expression of the exogenous β 1 subunit by an unknown mechanism (37). …”
Section: Discussionmentioning
confidence: 99%
“…As suggested by previous reports 21, 24 , we demonstrate that a true overexpression of either α isoform is impossible, since increased expression of one isoform results in compensatory down-regulation of the other endogenous α isoform. However, increased expression of the α2 isoform, which effectively results in replacement of α1 with α2, attenuated the hypertrophic response after transverse aortic constriction (TAC) and was associated with faster Ca 2+ extrusion via NCX1.…”
Section: Introductionsupporting
confidence: 78%
“…Previous work has suggested that a change in expression of a particular NKA isoform is balanced by altered expression of the other, such that a constant level of NKA protein is maintained 21, 24 . In agreement with these previous observations, our Western blot experiments from whole-cell extracts of NKA-α1, NKA-α2 and Wt hearts demonstrated that overexpression of one NKA isoform elicited downregulation of the other isoform in a manner that preserved total levels of NKA (Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note a major difference between our expression system and commonly used mammalian expression systems. For example, studies that have specifically investigated this issue have reported that the level of expression of endogenous ␣1 in COS-1, HEK-293, or MDCK cells is about 50% of total Na-K-ATPase ␣1 (8,43). Given the high level of endogenous ␣1, most assays have to be conducted in the presence of ouabain (e.g., 10 M) to eliminate the contribution from endogenous ␣1 Na-K-ATPase.…”
Section: Discussionmentioning
confidence: 99%